Implementasi Undang-Undang ITE dan Penerapan Restorative Justice Dalam Kasus-Kasus Hoax, Pornografi, Berita: Studi Karyawan BP Batam di Wilayah Polda Kepulauan Riau - Prisgunanto, Ilham; Sinaga, Saut Panggabean (Prisani Cendekia, 2025)
Crimes in the cyber world have developed significantly over time. The Indonesian government issued Law No. 11 of 2008 to regulate this. It covers crimes ranging from electronic transaction fraud, hoaxes, hate speech, online pornography, to cyberbullying. This article explains socialization campaign activities related to the implementation of the ITE Law in human life. Many people have not yet understood the legal aspects and reportable offenses that can be taken action against when there is deviant behavior in the use of internet networks. This community service uses outreach methods and information sharing with all parties within the BP Batam environment in the Riau Islands and the jurisdiction of the Riau Islands Police. The results indicate that it is indeed necessary to conduct hands-on practice in understanding misleading narrative content that sometimes triggers sensitive issues in the community, in an effort to strengthen social interactions between the community and the police. As a result, the synergy between the police and the community can be applied in the field. Therefore, there is a need for outreach and socialization regarding the world of cybercrime in society.